Use of unmanned ground vehicle systems in urbanized zones: A study of vector Mosquito surveillance in Kaohsiung - Yu-Xuan Chen; Chao-Ying Pan; Bo-Yu Chen; Shu-Wen Jeng; Chun-Hong Chen; Joh-Jong Huang; Chaur-Dong Chen; Wei-Liang Liu (Public Library of Science (PLoS), 2023)
Dengue fever is a vector-borne disease that has become a serious global public health problem over the past decade. An essential aspect of controlling and preventing mosquito-borne diseases is reduction of mosquito density. Through the process of urbanization, sewers (ditches) have become easy breeding sources of vector mosquitoes. In this study, we, for the first time, used unmanned ground vehicle systems (UGVs) to enter ditches in urban areas to observe vector mosquito ecology. We found traces of vector mosquitoes in ~20.7% of inspected ditches, suggesting that these constitute viable breeding sources of vector mosquitoes in urban areas. We also analyzed the average gravitrap catch of five administrative districts in Kaohsiung city from May to August 2018. The gravitrap indices of Nanzi and Fengshan districts were above the expected average (3.26), indicating that the vector mosquitoes density in these areas is high. Using the UGVs to detect positive ditches within the five districts followed by insecticide application generally yielded good control results. Further improving the high-resolution digital camera and spraying system of the UGVs may be able to effectively and instantly monitor vector mosquitoes and implement spraying controls. This approach may be suitable to solve the complex and difficult task of detecting mosquito breeding sources in urban ditches. Author summary In recent years, many countries have used new technologies to prevent dengue fever, among which unmanned vehicle systems are the most promising. We combined a crawling robot, wire-controlled cable car and real-time monitoring system into an unmanned ground vehicle system (UGV) to conduct ecological surveys of vector mosquitoes in sewers (ditches). The study found that the ditches in Kaohsiung city were a breeding source for dengue vector mosquitoes. Inspection by UGVs determined that 12 of the 58 examined ditches contained Aedes mosquitoes in stages from larvae to adult. Positive ditches were then sprayed with insecticides or flushed with high-temperature water jets to prevent the proliferation of mosquitoes. The widespread use of UGVs can potentially eliminate some of the breeding sources of vector mosquitoes, thereby reducing the annual prevalence of dengue fever in Kaohsiung city.